Analysis of Child Friendly School in bullying prevention in kindergarten - Rohati, Feri Mamae; Widyasari, Choiriyah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study explains the bullying prevention program implemented in a Child Friendly School (SRA) setting, focusing on how phenomenological inquiry can uncover students’ lived experiences of bullying and the ways the school’s initiatives give meaning to those experiences. Methodology: Employing a qualitative phenomenological design, data were collected through in‑depth interviews with teachers, parents, and students; direct observations of classroom and playground interactions; and review of relevant documentation (including SOPs and project plans). This approach allowed the researcher to interpret and describe the firsthand experiences of community members as they engage with the school’s anti‑bullying efforts. Results: Findings reveal that KB/TK Islam Orbit II’s bullying prevention program is guided by a clear Standard Operating Procedure (SOP) and is integrated into a Project‑Based Learning (PJBL) model that emphasizes collaboration, mutual assistance, and real‑world problem solving. Teachers serve as living models of positive behavior, instilling good habits in school that extend into the home. Moreover, by educating children about the nature, causes, and consequences of bullying, the program empowers peers to intervene when they witness harmful behavior. Parental involvement—marked by sensitivity to even minor physical or emotional changes in their children—emerged as a critical factor in early detection and intervention. Applications/Originality/Value: This study offers a replicable framework for schools seeking to create child‑centered anti‑bullying programs: combining clear procedural guidelines with experiential, project‑based learning and active role modeling. Its phenomenological insights into children’s and parents’ perceptions provide valuable guidance for educators and policymakers aiming to foster safer, more empathetic learning environments at both school and family levels.